The Impact of Bariatric Surgery on Type 2 Diabetes Mellitus and the Management of Hypoglycemic Events - Kassem, Mahmoud Attia Mohamed; Durda, Michael Andrew; Stoicea, Nicoleta; Cavus, Omer; Sahin, Levent; Rogers, Barbara (Frontiers in Endocrinology, 2017)
Recent studies discussed the benefit of bariatric surgery on obese patients diagnosed with type 2 diabetes mellitus(T2DM). Several factors play an essential role in predicting the impact of bariatric surgery on T2DM, such as ABCD score (age, BMI, C-peptide and duration of the disease), HbA1C, fasting blood glucose, incretins [Glucagon-like peptide-1 (GLP-1) and gastric inhibitory peptide (GIP)]. Restrictive-malabsorptive procedures are most effective in treating T2DM patients based on changes induced in appetite through regulation of gastro-intestinal hormones, with decreased hunger and increased satiation. We propose a review of bariatric surgery influence on T2DM and post-intervention hypoglycemic events. An extensive literature search was conducted on PubMed and Google Scholar using key words such as gastric bypass, T2DM, bariatric surgery, GLP-1, GIP, and post bariatric hypoglycemia. Conclusion: Post bariatric surgery hypoglycemia (PBH) is a serious complication especially when patients develop life-threatening neuroglycopenia with loss of consciousness and seizure. The avoidance of this adverse event may be achieved by strict dietary modification including a restriction on carbohydrates as well as foods with high glycemic index. Further research will provide more information on post bariatric surgery hyperinsulinemic hypoglycemia pathophysiology and management.